Pension Reform in the Baltics : Issues and Prospects - Schiff, Jerald; Hobdari, Niko.; Schimmelpfennig, Axel.; Zytek, Roman (Washington, D.C. : International Monetary Fund, 2001)
This paper provides an overview of efforts in the Baltic countries to reform their pension systems, and examines the choices facing these countries in their continued reform efforts. Early reforms were aimed at correcting the flaws of the inherited Soviet system and, in particular, at shoring up the finances of the pension systems and reducing their distortionary impact. The Baltic countries have been in the forefront of transition economies in their pursuit of pension reform. They have taken important steps to shore up the long-run financial health of their existing pension funds and made preparations for the implementation of a three-pillar scheme. Although a move toward a fully funded pension system can potentially make an important contribution to the objectives of pension reform, such a change is neither necessary nor sufficient to meet these goals. The existing PAYG pension system can, at least in theory, be made sustainable by an appropriate adjustment of payroll tax rates and expected lifetime pension benefits, although the average replacement rate implied by such changes may well be fairly low, reflecting the expected demographic developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet